REFLECTIVE APPROACH IN TEACHING FINE ARTS AND THE TEACHER’S PERSONAL COMPETENCE - Shovdirov Sunnat Aslanovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the importance of the reflective approach in teaching fine arts and its relationship with the development of a teacher’s personal competence. The reflective approach encourages teachers to analyze their own teaching experiences, evaluate their interactions with students, and make conscious improvements to their instructional methods. In fine arts education, reflection serves as both a creative and pedagogical tool that enables teachers to better understand students’ artistic development, emotional responses, and learning needs. The study highlights that reflective practice contributes to the formation of professional identity, self-awareness, and emotional intelligence, which are central elements of personal competence. It also examines the ways in which reflection enhances creativity, critical thinking, and adaptability in the teaching process. The article concludes that integrating reflective approaches into teacher training programs is essential for preparing competent, innovative, and self-directed fine arts educators.